Pengaruh Promosi Media Sosial dan Endorsement Food Content Creator terhadap Keputusan Pembelian - Reni Suci Wahyuni; Ahmad Syarif Mutsanna (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of social media promotion and food content creator endorsements on consumer purchasing decisions for Raja Cireng products in Kebumen. The method used in this study is a quantitative approach with a survey technique through the distribution of questionnaires to 100 respondents. Data analysis was conducted using multiple linear regression with the help of SPSS software. The results show that partially, neither social media promotion nor food content creator endorsements have a significant effect on purchasing decisions. Simultaneously, both variables also have no significant effect, with a coefficient of determination (R²) of 0.027 or 2.7%, which means that only a small portion of purchasing decisions can be explained by these two variables. This finding indicates that the digital promotion strategy used has not been effective in influencing consumer purchasing behavior in local areas such as Kebumen. This study provides implications that marketing approaches need to be adapted to the demographic characteristics and preferences of local consumers to achieve more optimal results.